Pelatihan Pembuatan Modul Berbasis Kurikulum 2013 bagi Guru di Kabupaten Magetan - Durinta Puspasari; Durinda Puspasari; Choirul Nikmah; Brillian Rosy (Universitas Negeri Surabaya, 2021)
The 2013 curriculum-based teaching materials making training is a means to improve the ability of teachers in making teaching materials that are relevant to the 2013 curriculum. So the teacher does not have a reference in learning. This training was given to vocational teachers in the Office Administration Skills Program in Magetan Regency. The purpose of the activity is 1) giving teachers knowledge about the 2013 curriculum and relevant teaching materials; 2) provide assignments for the preparation of modules based on 2013 Curriculum; 3) provide assistance to teachers to develop modules that are relevant to the 2013 Curriculum. The method of implementing PKM is by way of training and mentoring to teachers.The implementation of PKM consists of stages: 1) the delivery of material related to educational objectives based on the 2013 curriculum, the nature of learning, the understanding of teaching materials, and modules; 2) mentoring the making of curriculum-based learning modules in 2013. Keywords: training, modules, curriculum 2013